Le Hodna occidental entre régions méditerranéennes et plaines désertiques : organisation des terroirs, communautés rurales et productions agricoles au Moyen Âge - Mohamed Meouak (Revue des Mondes Musulmans et de la Méditerranée)
The aim of our contribution is based on two methodological points : to propose a critical reading of the Arabic sources and to give a precise picture of the soils in the western Hodna which is located between the maritim area of the Kabylie and the desert zones of the medieval central Maghreb. In a first time, we concentrate our efforts on the places of activities by the rural comunities for establishing a survey of the different settlement's structures. In a second chapter, we deal with the question of main aspects of the tribal organization as motor of the rural settlement in the western Hodna with a fondamental presence of Arab's groups, Berber's tribes and others « foreigners ». At last, in a third stage, we try to draw up a picture of the rural landscapes and the farm productions puting the emphasis mainly on the management of the farm spaces..